Comparison between Single and Dual Femoral Fixation for Anterior Cruciate Ligament Reconstruction with a Hamstring Autograft - Kim, Jin Goo (The Korean Knee Society, 2011)
PURPOSE: The purpose of this study was to evaluate dual fixation with different fixation mechanisms, determine the advantages, and compare the outcomes between single and dual femoral fixation. MATERIALS AND METHODS: From April 2004 to September 2007, 19 patients who received single femoral fixation and 22 patients who received dual femoral fixation were enrolled in the study. Single femoral fixation was performed using a cross-pin expansion mechanism. Dual femoral fixation was performed using a cross-pin expansion mechanism and an EndoButton CL loop suspensory mechanism. RESULTS: No significant differences were found in the incidence of cross-pin problems between the two groups (p=0.35-0.83) or in the stability assessment using a KT-2000 arthrometer and pivot shift test preoperatively (p=0.79 and 0.77, respectively) or postoperatively (p=0.89 and 0.75, respectively). In addition, no significant differences were detected between the two groups in the Lysholm, Tegner activity, or International Knee Documentation Committee knee scores preoperatively (p=0.07-0.47) or postoperatively (p=0.15-0.89). CONCLUSIONS: This study showed that dual fixation with different fixation mechanisms was not advantageous over the single fixation mechanism. Outcomes using the dual femoral fixation mechanism were not superior to those using the single femoral fixation mechanism.